2017
DOI: 10.1002/admi.201700583
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Hierarchical Porous Carbon Architecture Incorporated with Cobalt Nanoparticles and Carbon Nanotubes as Efficient Electrocatalyst for Oxygen Reduction Reaction

Abstract: Hierarchical porous carbon has attracted great interest because of its distinctive structure and superior properties for designing electrochemical energy storage and conversion devices. In this work, a novel method to fabricate nitrogen‐doped hierarchical porous carbon (NHPC) is reported, which is incorporated with Co nanoparticles and carbon nanotubes (CNTs). The NHPC is prepared using a facile and scalable MgO–Co template method. Metal nitrate–glycine solution combustion synthesis, followed by a high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 75 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…It is noted that the pyrolysis of the nitrate-starch gel is a well-known solution combustion synthesis (SCS) process, which generates an exothermic and self-sustaining redox reaction with the emission of a large amount of gases in a short time. The SCS reaction condition was evaluated according to the calculation of equivalence ratio, ϕ, which is the ratio of the total valencies of fuels to nitrate oxidizers. Here, a ϕ value larger than 1 represents a fuel-rich condition in a conventional SCS process in air/oxygen atmosphere. The ϕ values were calculated to be 1.20, 1.44, 1.92, and 2.40 for starch amount of st05, st06, st08, and st10, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is noted that the pyrolysis of the nitrate-starch gel is a well-known solution combustion synthesis (SCS) process, which generates an exothermic and self-sustaining redox reaction with the emission of a large amount of gases in a short time. The SCS reaction condition was evaluated according to the calculation of equivalence ratio, ϕ, which is the ratio of the total valencies of fuels to nitrate oxidizers. Here, a ϕ value larger than 1 represents a fuel-rich condition in a conventional SCS process in air/oxygen atmosphere. The ϕ values were calculated to be 1.20, 1.44, 1.92, and 2.40 for starch amount of st05, st06, st08, and st10, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The electrocatalytic performance of the decorated graphene should arise from the high specific surface area. However, many studies reported that the metal aggregation during high‐temperature pyrolysis processes probably decreases electrocatalytic activity . Therefore, graphene with highly‐dispersed CoN x species could be an ideal electrocatalyst if metal nanoparticles are prevented from aggregating during carbonization …”
Section: Methodsmentioning
confidence: 99%
“…42 Furthermore, glycine (NH 2 −CH 2 −COOH) was used both as the carbon and nitrogen source to stabilize the transition metals by interacting with the −NH 2 group in glycine, which may reduce the reaction energy barrier at the rate-determining step (RDS). 43 We argued that with the synergistic advantages of an adjustable hierarchical porous structure, a high electrochemical active surface area (ECSA), and Ni−N interactions, the as-prepared Ni@MicroPNC should exhibit enhanced ECO2RR performances.…”
Section: Introductionmentioning
confidence: 99%